Effects of Low Reynolds Number on Wake-Generated Unsteady Flow of an Axial-Flow Turbine Rotor - Matsunuma Takayuki; Tsutsui Yasukata (International Journal of Rotating Machinery)
The unsteady flow field downstream of axial-flow turbine rotors at low Reynolds numbers was investigated experimentally using hot-wire probes. Reynolds number, based on rotor exit velocity and rotor chord length Re <mtext>out</mtext>,<mtext>RT</mtext> , was varied from 3.2× 10 4 to 12.8× 10 4 at intervals of 1.0× 10 4 by changing the flow velocity of the wind tunnel. The time-averaged and time-dependent distributions of velocity and turbulence intensity were analyzed to determine the effect of Reynolds number. The reduction of Reynolds number had a marked influence on the turbine flow field. The regions of high turbulence intensity due to the wake and the secondary vortices were increased dramatically with the decreasing Reynolds number. The periodic fluctuation of the flow due to rotor-stator interaction also increased with the decreasing Reynolds number. The energy-dissipation thickness of the rotor midspan wake at the low Reynolds number Re <mtext>out</mtext>,<mtext>RT</mtext> =3.2× 10 4 was 1.5 times larger than that at the high Reynolds number Re <mtext>out</mtext>,<mtext>RT</mtext> =12.8× 10 4 . The curve of the −0.2 power of the Reynolds number agreed with the measured energy-dissipation thickness at higher Reynolds numbers. However, the curve of the −0.4 power law fitted more closely than the curve of the −0.2 power law at lower Reynolds numbers below 6.4× 10 4 .